Diagnostic Accuracy of Mammography Versus Ultrasound and Clinical Examination in the Prediction of Malignancy of Breast in Women Presenting with Palpable Breast Lesions, Taking Histopathology as Gold Standard - Fatima Masood; Saad Qayyum; Hafiz Muhammad Bilal (Indus Journal of Bioscience Research, 2025)
Objectives: The purpose of the study is to evaluate the diagnostic accuracy of clinical examination and ultrasound vs mammography in predicting breast cancer in women who report with palpable breast lesions. Study design: Cross-sectional (validation) study. Settings: Radiology department of Shalamar Hospital, Lahore. Study design: March 2025 to May 2025 Methodology: The study comprised 130 patients, ages 25 to 70 with breast lumps who were scheduled to have a TruCut core biopsy. Women who were unmarried, had previously received a breast cancer diagnosis, had a recurrence of the disease in the same location, and were receiving chemotherapy or radiation on the same side were not included. The screen film technique and specialized mammography equipment were used to do the mammogram.  Typical craniocaudal and mediolateral oblique views of the breast, as well as spot views, when necessary, were part of traditional four-view film mammograms. Knowing the clinical and mammographic results, a bilateral whole-breast ultrasound was conducted. A 7.5-MHZ frequency transducer probe and high resolution diagnostic ultrasonography equipment was used to obtain all sonograms. Mammography, and the presence or absence of malignant breast lesions on ultrasonography plus clinical examination were observed.  After that, every patient had a biopsy in the relevant department, and the results were compared to those from mammography and ultrasound. Results: Ultrasound and clinical examination sensitivity was (91.03%), specificity (82.69%), PPV (88.75%), NPV (86.0%), and diagnostic accuracy (87.69%) in detecting breast cancer. Mammography sensitivity was (92.11%), specificity (85.19%), PPV (89.76%), NPV (88.46%), and diagnostic accuracy (89.23%) in detecting breast cancer. Conclusion: Despite the fact that both mammography and ultrasound were proven to be specific, mammography was thought to have superior sensitivity and diagnostic accuracy.